2017
DOI: 10.1007/s10974-017-9473-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute high-caffeine exposure increases autophagic flux and reduces protein synthesis in C2C12 skeletal myotubes

Abstract: Caffeine is a highly catabolic dietary stimulant. High caffeine concentrations (1–10 mM) have previously been shown to inhibit protein synthesis and increase protein degradation in various mammalian cell lines. The purpose of this study was to examine the effect of short-term caffeine exposure on cell signaling pathways that regulate protein metabolism in mammalian skeletal muscle cells. Fully differentiated C2C12 skeletal myotubes either received vehicle (DMSO) or 5 mM caffeine for 6 h. Our analysis revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…To the best of our knowledge, the present study provides the first evidence that chronic caffeine treatment protects against mutant α-Syn-mediated neurotoxicity by re-establishing macroautophagy signals. This finding is in line with the view that caffeine induces a starvation response with induction of macroautophagy in yeasts (Winter et al, 2008 ; Saiki et al, 2011 ) and induce autophagy in various mammalian cell lines (Mathew et al, 2014 ; Hughes et al, 2017 ). In agreement with this view, caffeine reduces intra-hepatic lipid content and stimulates β-oxidation in hepatic cells with concomitant increase of autophagy and lipid uptake in lysosomes by down-regulation of mammalian target of rapamycin signaling (Sinha et al, 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…To the best of our knowledge, the present study provides the first evidence that chronic caffeine treatment protects against mutant α-Syn-mediated neurotoxicity by re-establishing macroautophagy signals. This finding is in line with the view that caffeine induces a starvation response with induction of macroautophagy in yeasts (Winter et al, 2008 ; Saiki et al, 2011 ) and induce autophagy in various mammalian cell lines (Mathew et al, 2014 ; Hughes et al, 2017 ). In agreement with this view, caffeine reduces intra-hepatic lipid content and stimulates β-oxidation in hepatic cells with concomitant increase of autophagy and lipid uptake in lysosomes by down-regulation of mammalian target of rapamycin signaling (Sinha et al, 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, we discovered that 0.5 mM caffeine promoted a twofold increase in autophagosome accumulation in 0.5 mM OA‐treated cells (Figure ). Although we have previously demonstrated that caffeine increases autophagy in skeletal myotubes (Hughes et al, ; Mathew et al, ), to the best of our knowledge this is the first investigation to demonstrate that a physiologically relevant dose of caffeine can significantly increase autophagy in mammalian skeletal myotubes.…”
Section: Discussionmentioning
confidence: 61%
“…The popular dietary stimulant caffeine has been shown to increase lipid utilization, mitochondrial biogenesis, and autophagy in skeletal muscle cells treated with very high doses of caffeine (Abbott, Edelman, & Turcotte, ; Ding et al, ; Hughes et al, ; Mathew et al, ). It remains unclear whether lower, more physiologically relevant doses of caffeine can similarly impact lipid metabolism and autophagy in mammalian skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, caffeine-enhanced autophagic flux in hepatic stellate cells was stimulated by endoplasmic reticulum (ER) stress via the IRE1-α signaling pathway, and autophagy trigged by caffeine instigated cell apoptosis (Li et al, 2017). Acute high-caffeine exposure also significantly reduced skeletal myotube diameter by increasing autophagic flux in differentiated C2C12 mouse skeletal myoblasts cells (Bloemberg and Quadrilatero, 2016;Hughes et al, 2017). Notably, caffeine increased autophagy by promoting the calcium-dependent activation of AMPactivated protein kinase (AMPK) in mammalian skeletal muscle cells (Mathew et al, 2014), and prevent skin from oxidative stress-induced senescence through the activation of autophagy.…”
Section: Caffeine May Modulate Pd Pathology By Regulating Autophagy Amentioning
confidence: 99%